Improvement of Shear Strength of Recycled Concrete Aggregate with MICP Treatment - Pholtrai, Rujira; Prongmanee, Nutthachai; Noulmanee, Amorndech; Supaso, Thawatchai (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
The increasing demand for sustainable construction materials has heightened interest in recycled concrete aggregate (RCA) as an alternative to natural crushed rock. However, RCA’s broader adoption in geotechnical applications remains limited by concerns about its mechanical properties, particularly shear strength and stability. This study assesses the shear strength and compaction characteristics of untreated RCA, MICP-treated RCA, and conventional crushed rock using a large-scale direct shear test with a 15 cm diameter circular shear box. Microbially Induced Calcite Precipitation (MICP) enhanced interparticle bonding and shear resistance. Under varying normal stresses, parameters including peak and residual shear strength, cohesion (c), internal friction angle (ϕ), and maximum dry density (γd, max) were evaluated. Results indicate that untreated RCA exhibits lower shear strength than MICP-treated RCA, primarily due to residual cement paste and weaker particle interlocking. Conversely, MICP treatment significantly improves RCA’s cohesion and peak shear strength, confirming its potential as a sustainable replacement for natural aggregates. Despite a slight reduction in friction angle and maximum dry density due to altered particle packing efficiency from calcium carbonate (CaCO3) precipitation, MICP-treated RCA displayed enhanced resistance to post-peak strength loss, resulting in consistently higher residual shear strength. Therefore, the bio-stabilization provided by MICP emerges as a promising, environmentally friendly alternative to traditional chemical stabilizers, supporting the reuse of construction waste materials. Further optimization to balance cohesion gains with frictional properties is recommended to enhance the competitive performance of MICP-treated RCA against natural aggregates. This call for further optimization challenges the audience, encouraging them to contribute to the advancement of eco-friendly soil stabilization methods and the promotion of circular economy practices in the construction industry.